The role of financial literacy and self-control: risky credit behavior in using paylater - Rismaya, Rismaya; Ullum, Miftahul; Mardiyani, Mardiyani (Manajemen dan Bisnis, 2025)
In an increasingly digital era, credit is more accessible, which can potentially lead to risky credit behavior. It is to analyze how financial technology and financial literacy influence risky credit behavior where self-control is a mediating variable. The research method uses quantitative research, causal associative research type the total sample size is 150 respondents. Data gathered was carried out by distributing online questionnaires and then analyzed with PLS-SEM. The results stated that financial technology and financial literacy significantly affect risky credit behavior. Meanwhile, the mediating variable that strengthens the correlation between fintech and risky credit behavior is self-control. This indicates that financial literacy and self-control are very influential in minimizing the negative impact of using financial technology such as PayLater, namely risky credit behavior. There is a need to increase financial literacy among Pay Later users and education related to self-control in using digital credit services to reduce the occurrence of risky credit behavior.